Nupr1 Modulates Methamphetamine-Induced Dopaminergic Neuronal Apoptosis and Autophagy through CHOP-Trib3-Mediated Endoplasmic Reticulum Stress Signaling Pathway - Xu, Xiang; Huang, Enping; Tai, Yunchun; Zhao, Xu; Chen, Xuebing; Chen, Chuanxiang; Chen, Rui; Liu, Chao; Lin, Zhoumeng; Wang, Huijun; Xie, Wei-Bing (Frontiers in Molecular Neuroscience, 2017)
Methamphetamine (METH) is an illegal and widely abused psychoactive stimulant. METH exposure causes detrimental effects on multiple organ systems, primarily the nervous system, especially dopaminergic pathways, in both laboratory animals and humans. In this study, we hypothesized that Nuclear protein 1 (Nupr1/com1/p8) is involved in METH-induced neuronal apoptosis and autophagy through endoplasmic reticulum (ER) stress signaling pathway. To test this hypothesis, we measured the expression levels of Nupr1, ER stress protein markers CHOP and Trib3, apoptosis-related protein markers cleaved-caspase3 and PARP, as well as autophagy-related protein markers LC3 and Beclin-1 in brain tissues of adult male Sprague-Dawley (SD) rats, rat primary cultured neurons and the rat adrenal pheochromocytoma cells (PC12 cells) after METH exposure. We also determined the effects of METH exposure on the expression of these proteins after silencing Nupr1, CHOP, or Trib3 expression with synthetic small hairpin RNA (shRNA) or siRNA in vitro, and after silencing Nupr1 in the striatum of rats by injecting lentivirus containing shRNA sequence targeting Nupr1 gene to rat striatum. The results showed that METH exposure increased Nupr1 expression that was accompanied with increased expression of ER stress protein markers CHOP and Trib3, and also led to apoptosis and autophagy in rat primary neurons and in PC12 cells after 24 h exposure (3.0 mM), and in the prefrontal cortex and striatum of rats after repeated intraperitoneal injections (15 mg/kg × 8 injections at 12 h intervals). Silencing of Nupr1 expression partly reduced METH-induced apoptosis and autophagy in vitro and in vivo. These results suggest that Nupr1 plays an essential role in METH-caused neuronal apoptosis and autophagy at relatively higher doses and may be a potential therapeutic target in high-dose METH-induced neurotoxicity.